2017
DOI: 10.1371/journal.ppat.1006439
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Erlin-dependent release of the B12 transmembrane J-protein promotes ER membrane penetration of a non-enveloped virus

Abstract: The molecular mechanism by which non-enveloped viruses penetrate biological membranes remains enigmatic. The non-enveloped polyomavirus SV40 penetrates the endoplasmic reticulum (ER) membrane to reach the cytosol and cause infection. We previously demonstrated that SV40 creates its own membrane penetration structure by mobilizing select transmembrane proteins to distinct puncta in the ER membrane called foci that likely function as the cytosol entry sites. How these ER membrane proteins reorganize into the foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…When the FLAG-tagged proteins were immunoprecipitated, endogenous Hsc70 was found in the WT B12-FLAG-but not the QPD B12-FLAG-precipitated sample (Fig. 1D, second row from top), indicating that WT B12, but not QPD B12, binds to Hsc70, as previously reported (31). Importantly, endogenous Bag2 was observed in the WT B12-FLAGprecipitated but minimally in the QPD B12-FLAG-precipitated material ( Fig.…”
supporting
confidence: 83%
“…When the FLAG-tagged proteins were immunoprecipitated, endogenous Hsc70 was found in the WT B12-FLAG-but not the QPD B12-FLAG-precipitated sample (Fig. 1D, second row from top), indicating that WT B12, but not QPD B12, binds to Hsc70, as previously reported (31). Importantly, endogenous Bag2 was observed in the WT B12-FLAGprecipitated but minimally in the QPD B12-FLAG-precipitated material ( Fig.…”
supporting
confidence: 83%
“…Importantly, in the same MS analysis, peptides corresponding to the ER membrane protein RTN4 were present in the 3xFLAG-B12 precipitated material, while peptides corresponding to RTN4 and RTN3 were identified in the 3xFLAG-C18 precipitated samples (Fig. 1 a; Bagchi et al, 2015;Inoue and Tsai, 2017); no peptides matching RTN3 or RTN4 were found in precipitated material derived from parental cells not expressing FLAG-tagged protein. To confirm that B12 and C18, as well as B14, associate with RTN3 or RTN4, anti-FLAG precipitations from parental cells and cells expressing 3xFLAG-B12, 3xFLAG-B14, or 3xFLAG-C18 were analyzed by SDS-PAGE and immunoblotting, with the precipitated material found to contain endogenous RTN4B ( Fig.…”
Section: Rtn4 Binds To the Er Membrane J Proteins B12 B14 And C18mentioning
confidence: 76%
“…They oligomerize into a toroidal, ~2MDa complex, to which RNF170 is constitutively bound (7,13,14). By far the best defined function of erlins to date is to mediate IP3R processing (7), but other possible roles have been proposed, including binding cholesterol (16), regulation of lipid metabolism (16,17), and regulation of proteins that mediate SV40 exit from the ER (18). Interestingly, mutations to erlin1 and, more commonly, erlin2 have been linked to rare neurodegenerative diseases; e.g.…”
Section: +mentioning
confidence: 99%